Disease monitoring strategies in inflammatory bowel diseases: What do we mean by ‘tight control’? - Gonczi, Lorant; Bessissow, Talat; Lakatos, Peter Laszlo (World journal of gastroenterology : WJG, 2019)
In recent years, there has been a critical change in treatment paradigms in inflammatory bowel diseases (IBD) triggered by the arrival of new effective treatments aiming to prevent disease progression, bowel damage and disability. The insufficiency of symptomatic disease control and the well-known discordance between symptoms and objective measures of disease activity lead to the need of reviewing conventional treatment algorithms and developing new concepts of optimal therapeutic strategy. The treat-to-target strategies, defined by the selecting therapeutic targets in inflammatory bowel disease consensus recommendation, move away from only symptomatic disease control and support targeting composite therapeutic endpoints (clinical and endoscopical remission) and timely assessment. Emerging data suggest that early therapy using a treat-to-target approach and an algorithmic therapy escalation using regular disease monitoring by clinical and biochemical markers (fecal calprotectin and C-reactive protein) leads to improved outcomes. This review aims to present the emerging strategies and supporting evidence in the current therapeutic paradigm of IBD including the concepts of "early intervention", "treat-to-target" and "tight control" strategies. We also discuss the real-word experience and applicability of these new strategies and give an overview on the future perspectives and areas in need of further research and potential improvement regarding treatment targets and ("tight") disease monitoring strategies.